Larval growth of the polychaete Arenicola marina under different temperature and food conditions: consequences on bioenergetic models. Issue 1 (9th June 2022) - Broquard, Coralie; Lancelot, Théo; Lefebvre, Sébastien; Courcot, Lucie; Gaudron, Sylvie M
Abstract : Biphasic growth models of Arenicola marina larvae highlight an optimal temperature at 15°C with a lower temperature tolerance range compared with juveniles and adults. We claim that two sets of Arrhenius temperatures depending on the life history stages should be implemented when using an abj-Dynamic Energy Budget model in this species. Abstract: Arenicola marina, a marine benthic polychaete, is widespread on sandy beaches in Europe and considered as an ecosystem engineer despite commonly used as bait by fishermen. Data regarding the bioenergetics of the lugworm larval stages are still incomplete. Trochophore is initially lecithotroph and then becomes planktotroph while growing as metatrochophore on subtidal area, a quite stable daily temperature environment compared with the foreshore, where juveniles and adult live, with daily temperature fluctuating up to 15°C. These discrepancies in temperature ranges may influence the temperature corrections (TCs) that control metabolic rates during the life cycle of A. marina . We carried out laboratory experiments in microcosms by inducing artificial spawning of lugworms, and then undertaken in vitro fertilization to obtain embryos and, finally, to follow, the larval development up to 10 segments with chaetae for 50 days under three temperature conditions (13°C, 15°C and 17°C) and two food conditions ('fed' and 'non-fed'). The first feeding ('birth') of A. marina larvae was deciphered anatomically for a size between 450 and 500 μm and described at 17 days post-fertilization for larvae reared at 15°C and 17°C. Using a biphasic model with a von Bertalanffy growth before 'birth' and an exponential growth after 'birth', among the three temperature treatments, the 15°C condition exhibited the best larval performance. TC based on embryonic and larval metabolic rates gave an Arrhenius temperature of 6661 K and a higher boundary temperature tolerance range of 294.5 K. Both temperature values differ from those calculated from TC based mostly on juvenile and adult metabolic rates. We claim to use two sets of Arrhenius temperatures according to the life history stages of A. marina while using Dynamic Energy Budget model. This model was developed initially in order to manage the conservation of the lugworm species.